The K+ Channel Opener 1-EBIO Potentiates Residual Function of Mutant CFTR in Rectal Biopsies from Cystic Fibrosis Patients - Roth, Eva K.; Hirtz, Stephanie; Duerr, Julia; Wenning, Daniel; Eichler, Irmgard; Seydewitz, Hans H.; Amaral, Margarida D.; Mall, Marcus A. (PLOS ONE, 2011)
Background The identification of strategies to improve mutant CFTR function remains a key priority in the development of new treatments for cystic fibrosis (CF). Previous studies demonstrated that the K+ channel opener 1-ethyl-2-benzimidazolone (1-EBIO) potentiates CFTR-mediated Cl− secretion in cultured cells and mouse colon. However, the effects of 1-EBIO on wild-type and mutant CFTR function in native human colonic tissues remain unknown. Methods We studied the effects of 1-EBIO on CFTR-mediated Cl− secretion in rectal biopsies from 47 CF patients carrying a wide spectrum of CFTR mutations and 57 age-matched controls. Rectal tissues were mounted in perfused micro-Ussing chambers and the effects of 1-EBIO were compared in control tissues, CF tissues expressing residual CFTR function and CF tissues with no detectable Cl− secretion. Results Studies in control tissues demonstrate that 1-EBIO activated CFTR-mediated Cl− secretion in the absence of cAMP-mediated stimulation and potentiated cAMP-induced Cl− secretion by 39.2±6.7% (P<0.001) via activation of basolateral Ca2+-activated and clotrimazole-sensitive KCNN4 K+ channels. In CF specimens, 1-EBIO potentiated cAMP-induced Cl− secretion in tissues with residual CFTR function by 44.4±11.5% (P<0.001), but had no effect on tissues lacking CFTR-mediated Cl−conductance. Conclusions We conclude that 1-EBIO potentiates Cl−secretion in native CF tissues expressing CFTR mutants with residual Cl− channel function by activation of basolateral KCNN4 K+ channels that increase the driving force for luminal Cl− exit. This mechanism may augment effects of CFTR correctors and potentiators that increase the number and/or activity of mutant CFTR channels at the cell surface and suggests KCNN4 as a therapeutic target for CF.